1993
DOI: 10.1353/sls.1993.0000
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Deletion Revisited: Errors in Young Children’s Two-Handed Signs

Abstract: The omission or deletion of one hand from two-handed signs was examined in 9 young children of deaf parents. The patterns of hand deletion found in the early signs of these children were quite similar to those reported by Battison (1974) for adult signers. Battison accounted for the deletion patterns he observed largely by sign symmetry. Analyses of the present children’s deletions, however, revealed that the likelihood of hand deletion was also highly related to the type of contact the sign required. Deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Moreover, distinct feature classes differ in their contribution to language processing. Location information, specifically, is particularly salient to lexical access (Emmorey and Corina, 1990 ; Corina and Hildebrandt, 2002 ; Thompson et al, 2005 ; Baus et al, 2008 ; Carreiras et al, 2008 ; Orfanidou et al, 2009 ; Gutiérrez et al, 2012 ); it provides a strong cue for similarity (Hildebrandt and Corina, 2002 ; Bochner et al, 2011 ); and it is acquired earlier (Siedlecki and Bonvillian, 1993 ) and more accurately (Marentette and Mayberry, 2000 ; Morgan, 2006 ) during first-language acquisition. Other studies have suggested that typical (Morgan, 2006 ; Morgan et al, 2007 ) and disordered (Marshall et al, 2006 ) acquisition of sign language is constrained by the complexity of features and their distance from the body (Meier, 2000 ; Meier et al, 2008 )—a factor also affecting adult signers (Poizner et al, 1981 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, distinct feature classes differ in their contribution to language processing. Location information, specifically, is particularly salient to lexical access (Emmorey and Corina, 1990 ; Corina and Hildebrandt, 2002 ; Thompson et al, 2005 ; Baus et al, 2008 ; Carreiras et al, 2008 ; Orfanidou et al, 2009 ; Gutiérrez et al, 2012 ); it provides a strong cue for similarity (Hildebrandt and Corina, 2002 ; Bochner et al, 2011 ); and it is acquired earlier (Siedlecki and Bonvillian, 1993 ) and more accurately (Marentette and Mayberry, 2000 ; Morgan, 2006 ) during first-language acquisition. Other studies have suggested that typical (Morgan, 2006 ; Morgan et al, 2007 ) and disordered (Marshall et al, 2006 ) acquisition of sign language is constrained by the complexity of features and their distance from the body (Meier, 2000 ; Meier et al, 2008 )—a factor also affecting adult signers (Poizner et al, 1981 ).…”
Section: Introductionmentioning
confidence: 99%
“…The interested reader is referred to Vennes (2018) for a recent review on weak drop and the related phenomenon of weak hand lowering). The same resistance to weak drop is observed in first-language acquisition (Siedlecki and Bonvillian, 1993). And the many linguistic processes that turn one-handed signs into two-handed signs result in signs with alternating, not symmetrical movements (Padden and Perlmutter, 1987).…”
Section: Introductionmentioning
confidence: 53%
“…However, if the two-handed sign has an alternating movement, weak drop is prohibited (see Battison, 1974;Brentari, 1998for ASL, van der Kooij et al, 2001 for the Sign Language of the Netherlands). And such signs resist weak drop not only in adult signers, but also in children acquiring sign language natively (Siedlecki and Bonvillian, 1993), suggesting that the reason for this resistance is indeed motoric and not language-internal (though iconicity may prevent weak drop as well, in cases where the alternating movement is motivated by the sign's semantics, van der Kooij et al, 2001). And in the processes that turn one-handed signs into two-handed signs, the output is two-handed signs with alternating movements (e.g., in the Characteristic Adjective derivation, where a sign meaning "X" turns into a sign with the meaning characteristically "X," Padden and Perlmutter, 1987).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Deletion of the non-dominant hand from symmetrical two-handed signs was significantly more frequent (29/135 target signs). Interestingly, Siedlecki and Bonvillian (1993) interpret their data to suggest that children's errors were constrained by whether distinctive phonological information would be lost. Cheek et al (2001) examined the prelinguistic gesture (including communicative gestures and "manual babbles") of ten children, five sign-naïve hearing infants and five deaf infants born to deaf, ASL-signing parents.…”
Section: Acquisition Of Two-handed Signs By Deaf Childrenmentioning
confidence: 99%